Functional characterization of Fagopyrum tataricum ZIP gene family as a metal ion transporter - Zhang, Xinrong; Kong, Jiao; Yu, Lingzhi; Wang, Anhu; Yang, Yi; Li, Xiaoyi; Wang, Jianmei (Frontiers in Plant Science, 2024)
The zinc/iron-regulated transporter-like proteins (ZIP) family acts as an important transporter for divalent metal cations such as Zn, Fe, Mn, Cu, and even Cd. However, their condition is unclear in Tartary buckwheat (Fagopyrum tataricum). Here, 13 ZIP proteins were identified and were predicted to be mostly plasma membrane-localized. The transient expressions of FtZIP2 and FtZIP6 in tobacco confirmed the prediction. Multiple sequence alignment analysis of FtZIP proteins revealed that most of them had 8 putative transmembrane (TM) domains and a variable region rich in histidine residues between TM3 and TM4, indicating the reliable affinity to metal ions. Gene expression analysis by qRT-PCR showed that FtZIP genes were markedly different in different organs, such as roots, stems, leaves, flowers, fruits and seeds. However, in seedlings, the relative expression of FtZIP10 was notably induced under the CdCl2 treatment, while excessive Zn 2+ , Fe 2+ , Mn 2+ and Cd 2+ increased the transcript of FtZIP5 or FtZIP13, in comparison to normal conditions. Complementation of yeast mutants with the FtZIP family genes demonstrate that FtZIP7/10/12 transport Zn, FtZIP5/6/7/9/10/11 transport Fe, FtZIP12 transports Mn and FtZIP2/3/4/7 transport Cd. Our data suggest that FtZIP proteins have conserved functions of transportation of metal ions but with distinct spatial expression levels.